Pengetahuan Ibu, Pola Makan Balita, dan Pendapatan Keluarga dengan Status Gizi pada Balita di Wilayah Kerja Puskesmas Danga Kecamatan Aesesa Kabupaten Nagekeo - Falerius Jago (Lontar : Journal of Community Health, 2019)
Aesesa Sub-district is one of the Subdistricts in Nagekeo District that has high nutritional problems and occurs every year.Nutrition problems that occur are influenced by several factors, namely mother's knowledge of nutrition, diet of children under five, and family income.This study aims to determine what factors are related to the nutritional status of children under five years in the working area of Puskesmas Danga, Aesesa Sub-district, Nagekeo Regency in 2016.This research was conducted in the working area of Puskesmas Danga, Aesesa Sub District, Nagekeo District.The study period starts from December 2016 to August 2017.This research method is analytic survey by using cross sectional study design.Sample in this research is mother who have toddler which amounted 93 people. Sampling method using systematic random sampling technique.Instrument of data collecting by using questioner and analyzed by univariat and bivariat.The results showed that there was a correlation between mother's knowledge (ρ = 0,003), diet (ρ = 0,000), and family income (ρ = 0,029) with nutritional status in toddler in working area of Puskesmas Danga Aesesa Sub-district of Nagekeo Regency 2016.Based on the results of this study, it can be concluded that there is a relationship between mother's knowledge about nutrition, eating pattern of children under five, and income of family with nutritional status at under five years in working area of Puskesmas Danga Aesesa District of Nagekeo Regency.